(untitled) (Fiep Bulletin - online, 2011)
The official anthem of the clubs from Rio de Janeiro, composes in the First Republic were influenced by the hygienist thought and military marches. The march "Ó Abre Alas", by Chiquinha Gonzaga seems to open the deployment of martial marches for carnival. The official anthem of Flamengo, apparently, is more popular than the others, possibly due to three factors: being in the format of a carnival march; having simple and popular language; by the club have sprung up faster than others. The research concluded that the official works are at risk of losing themselves with important fragments of the stories from the clubs and Rio de Janeiro society.